Transitivity Analysis in English for Logistics: A Systemic Functional Linguistic Study - Septiana, Ponia Mega; Yeni Yuliyanti, Ai; Sari, Titania (Humanis; Vol 27 No 3 (2023)DO - 10.24843/JH.2023.v27.i03.p04, 2023)
This study discusses the transitivity process. transitivity helps us in understanding the relationship between subject, object, and action in a sentence. This research aims to determine the process type of English clause in English for Logistics Books by Grussendorf (2009) . The data is obtained from six reading comprehension articles contained in the book. The main theory used a transitivity system based on Halliday & Matthiessen (2014b). The method used qualitative description. The result of this research states that four types of processes are used in this research. They are the material, mental, relational, and verbal processes. The dominant frequency of occurrence process in this research is the mental process as much as at 35%. This research may involve ESP teaching process, especially for Logistics Business Students.